"Why can´t women talk like a man?": an investigation of gender in the play Pygmalion by Bernard Shaw - Gallardo, Bárbara Cristina (2001)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão